Expanding the ethical debate on human artificial placenta trials - Alice Cavolo; Daniel Pizzolato (Research Ethics Review)
Artificial placentas (APs) are technologies that mimic the human placenta to treat extremely preterm infants. Being an invasive and risky technology, it will raise important ethical questions for human trials. Hence, in this Topic Piece we provide a blueprint of further issues to investigate. First, counselling will have the double role of providing trial information as well as (non) treatment counselling. This requires extra training and the development of ad hoc decision aids to support counselling and parents’ decision-making. Second, more stakeholder involvement is needed. Direct stakeholders, such as parents, clinicians, and researchers, can help develop the decision aids and provide insight on potentially overlooked issues. Society should also be involved to determine whether AP trials and implementation should be subsidized, and the ethical implications of not subsidizing. Third, a proper cost-benefit analysis should be conducted to determine the exact cost of the technology.